Disulfiram Produces Potent Anxiolytic-Like Effects Without Benzodiazepine Anxiolytics-Related Adverse Effects in Mice - Saitoh, Akiyoshi; Nagayama, Yoshifumi; Yamada, Daisuke; Makino, Kosho; Yoshioka, Toshinori; Yamanaka, Nanami; Nakatani, Momoka; Takahashi, Yoshino; Yamazaki, Mayuna; Shigemoto, Chihiro; Ohashi, Misaki; Okano, Kotaro; et al. (Frontiers in Pharmacology, 2022)
Disulfiram is an FDA approved drug for the treatment of alcoholism. The drug acts by inhibiting aldehyde dehydrogenase, an enzyme essential to alcohol metabolism. However, a recent study has demonstrated that disulfiram also potently inhibits the cytoplasmic protein FROUNT, a common regulator of chemokine receptor CCR2 and CCR5 signaling. Several studies have reported that chemokine receptors are associated with the regulation of emotional behaviors in rodents, such as anxiety. Therefore, this study was performed to clarify the effect of disulfiram on emotional behavior in rodents. The anxiolytic-like effects of disulfiram were investigated using an elevated plus-maze (EPM) test, a typical screening model for anxiolytics. Disulfiram (40 or 80 mg/kg) significantly increased the amount of time spent in the open arms of the maze and the number of open arm entries without affecting the total open arms entries. Similar results were obtained in mice treated with a selective FROUNT inhibitor, disulfiram-41 (10 mg/kg). These disulfiram-associated behavioral changes were similar to those observed following treatment with the benzodiazepine anxiolytic diazepam (1.5 mg/kg). Moreover, disulfiram (40 mg/kg) significantly and completely attenuated increased extracellular glutamate levels in the prelimbic-prefrontal cortex (PL-PFC) during stress exposure on the elevated open-platform. However, no effect in the EPM test was seen following administration of the selective aldehyde dehydrogenase inhibitor cyanamide (40 mg/kg). In contrast to diazepam, disulfiram caused no sedation effects in the open-field, coordination disorder on a rotarod, or amnesia in a Y-maze. This is the first report suggesting that disulfiram produces anxiolytic-like effects in rodents. We found that the presynaptic inhibitory effects on glutaminergic neurons in the PL-PFC may be involved in its underlying mechanism. Disulfiram could therefore be an effective and novel anxiolytic drug that does not produce benzodiazepine-related adverse effects, such as amnesia, coordination disorder, or sedation, as found with diazepam. We propose that the inhibitory activity of disulfiram against FROUNT function provides an effective therapeutic option in anxiety.